Effectiveness of virtual learning system in agricultural education in India - Shravani, Kotha; Padaria, Rabindra Nath; Singh, Rashmi; Sarkar, Sujit; Praveen, K. V.; Varghese, Cini; Rakshit, Shantanu; Aishwarya, S.; Yadav, Preeti; Saini, Sushmita; Mukherjee, Sweety; Ghosh, Bhaskar; et al. (Frontiers in Education, 2025)
IntroductionVirtual learning systems (VLS) have become increasingly significant in agricultural education, especially for enhancing accessibility and flexibility. However, their effectiveness in improving learners’ engagement, satisfaction, retention, and overall outcomes remains uncertain, particularly within the Indian agricultural education context.MethodologyA cross-sectional study was conducted among 400 students from Undergraduate (UG), Postgraduate (PG), and PhD programs across randomly selected agricultural universities. Effectiveness Index was constructed using entropy method. Multiple linear regression analysis was employed to identify key predictors.ResultsThe findings indicate that 50.5% of students perceived a medium level of VLS effectiveness. Postgraduate and PhD students reported higher engagement and satisfaction than UG students. Self-regulation was the most significant predictor of learning effectiveness, followed by learners’ attitudes and e-learning design. Gender differences were also observed, with female students performing better in virtual learning environments.Discussion and conclusionThe study highlights the critical role of self-regulation, positive learners’ attitudes, and well-structured e-learning design in enhancing the effectiveness of virtual learning. These insights can inform the development of strategies aimed at optimizing virtual platforms for agricultural education.